Nanogenerators for wearable bioelectronics and biodevices. (25th October 2018) - Song, Peiyi; Yang, Guang; Lang, Tingting; Yong, Ken-Tye
Abstract: In this topical review, we will focus our discussion on the engineering of nanogenerators-related wearable bioelectronics and biodevices for diagnostic and therapeutic technologies. In the beginning, two most widely used nanogenerators, piezoelectric nanogenerator and triboelectric nanogenerator will be introduced, with a brief discussion of other power harvesting technologies. Subsequently, the design, fabrication and application guidelines for various nanogenerators will be presented and such information will allow one to conveniently engineer wearable, portable or implantable nanogenerator-based devices for specific detection or biomolecules delivery applications. In the third part of the review, we will discuss an array of examples of using different designed nanogenerators-related electronics and devices for pressure sensing, bio-sensing, motion monitoring, electrical treatment, cell/tissue/organ stimulation and drug delivery. Lastly, perspectives and challenges in further studies will be discussed.